Advances in CAR-NK cell therapy for hematological malignancies - Yang, Rui; Yang, Yun; Liu, Rui; Wang, Yiwen; Yang, Ruoyu; He, Aili (Frontiers in Immunology, 2024)
Chimeric antigen receptor T (CAR-T) cell therapy has revolutionized the treatment of hematological malignancies, demonstrably improving patient outcomes and prognosis. However, its application has introduced new challenges, such as safety concerns, offtarget toxicities, and significant costs. Natural killer (NK) cells are crucial components of the innate immune system, capable of eliminating tumor cells without prior exposure to specific antigens or pre-activation. This inherent advantage complements the limitations of T cells, making CAR-NK cell therapy a promising avenue for hematological tumor immunotherapy. In recent years, preclinical and clinical studies have yielded preliminary evidence supporting the safety and efficacy of CAR-NK cell therapy in hematological malignancies, paving the way for future advancements in immunotherapy. This review aims to succinctly discuss the characteristics, significant therapeutic progress, and potential challenges associated with CAR-NK cell therapy.